Human Physiology - Fox, Stuart Ira (New York McGraw-Hill, 2009)
Now in its 11th edition, Fox is one of the best-selling book in this market. Clear explanations and a solid learning framework have been market tested and refined. Fox help students master the fundamentals by providing appropriate anatomical detail.
Include Illustrations, Appendix, Glossary and Index.
Keywords: Human physiology -- Physiology